2011
DOI: 10.1371/journal.pone.0028129
|View full text |Cite
|
Sign up to set email alerts
|

Home Labour Induction with Retrievable Prostaglandin Pessary and Continuous Telemetric Trans-Abdominal Fetal ECG Monitoring

Abstract: ObjectiveTo evaluate the feasibility of continuous telemetric trans-abdominal fetal electrocardiogram (a-fECG) in women undergoing labour induction at home.Study DesignLow risk women with singleton term pregnancy undergoing labour induction with retrievable, slow-release dinoprostone pessaries (n = 70) were allowed home for up to 24 hours, while a-fECG and uterine activity were monitored in hospital via wireless technology. Semi-structured diaries were analysed using a combined descriptive and interpretive app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 11 publications
3
57
0
1
Order By: Relevance
“…Previous studies exploring women's experiences of outpatient cervical ripening or induction reported that women identified the ongoing support and presence of family members at home as comforting and beneficial [7,8,10]. Reported anxieties by participants in our study are therefore unsurprising.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Previous studies exploring women's experiences of outpatient cervical ripening or induction reported that women identified the ongoing support and presence of family members at home as comforting and beneficial [7,8,10]. Reported anxieties by participants in our study are therefore unsurprising.…”
Section: Discussionmentioning
confidence: 62%
“…Engagement with the research data revealed a strong sense that participants' experiences of the cervical ripening procedure were "undermined" in relation to the 4 overarching themes identified. Although women's dissatisfaction with labour induction [11][12][13]15] and increased satisfaction with outpatient cervical ripening [3,[6][7][8][9][10] have been previously reported in other studies, the notion of women's experiences being undermined during inpatient cervical ripening has not previously been identified in the literature reviewed. This may be due to the fact that there is a dearth of previous enquiry exploring women's experiences of inpatient cervical ripening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations